2019
DOI: 10.1039/c9ra01789e
|View full text |Cite
|
Sign up to set email alerts
|

Influence of air contamination during heat-assisted plasma treatment on adhesion properties of polytetrafluoroethylene (PTFE)

Abstract: We show that both applying a high temperature and decreasing the air concentration enhance the adhesion properties of polytetrafluoroethylene to isobutylene–isoprene rubber, but the adhesion properties decrease with increasing the air concentration during treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…In addition, studies have shown that thermally assisted plasma treatment of PTFE [210,211] can promote the formation of carbon-carbon crosslinks on the surface of PTFE and the etching of weak boundary layers, which greatly improves the adhesion strength of PTFE. Hamdi et al [212] found that when primer coating and UV/ozone radiation were applied, the adhesion of acrylonitrile butadiene styrene increased.…”
Section: Frictionmentioning
confidence: 99%
“…In addition, studies have shown that thermally assisted plasma treatment of PTFE [210,211] can promote the formation of carbon-carbon crosslinks on the surface of PTFE and the etching of weak boundary layers, which greatly improves the adhesion strength of PTFE. Hamdi et al [212] found that when primer coating and UV/ozone radiation were applied, the adhesion of acrylonitrile butadiene styrene increased.…”
Section: Frictionmentioning
confidence: 99%
“…The hydrogenation of alkenes takes place during the reaction between the modified surface of PTFE (−C=C−) and ethanol as a transposition of the Billups‐Birch mechanism applied to PTFE in the sodium naphthalenide based diglyme solution. The presence of −C−O and −O−C=O peaks comes from the surface contamination [28] …”
Section: Resultsmentioning
confidence: 99%
“…The combination of the results of the SEM observation and the surface hardness indicated that the WBL was removed from the He- or Ar-HAP-treated PTFE surface, respectively. It was reported that the surface hardness was 155 MPa when the plasma-treated PTFE surface had neither C–C crosslinks nor the WBL, while the surface hardness was 177 MPa when the plasma-treated PTFE surface had C–C crosslinks but no WBL [ 33 ]. In short, the report demonstrated that the factors that increase the surface hardness include the removal of a WBL and the increase in C–C crosslinks; the removal of a WBL induced an increase of 45 MPa, and the increase in C–C crosslinks induced an increase of 22 MPa in surface hardness.…”
Section: Resultsmentioning
confidence: 99%
“…When a WBL is removed and recovered from PTFE surface via plasma treatment, the PTFE surface hardness increases [ 33 ]. To double-check the presence or absence of a WBL, the surface hardness was measured before and after HAP treatment using a nanoindenter (ENT-2100, Elionix, Hachioji, Tokyo, Japan).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation